Test environments for large‐scale software systems—An industrial study of intrinsic and extrinsic success factors. (3rd January 2023) - Mårtensson, Torvald; Ancher, Göran; Ståhl, Daniel
Abstract: The characteristics of the test environment are of vital importance to its ability to support the organizations testing objectives. This paper seeks to address the need for a structured and reliable approach, which can be used by companies and other organizations to optimize their test environments in each individual case. The reported study included a series of interviews with 30 individuals, a series of focus groups with in total 31 individuals and a cross‐company workshop with 30 participants from five large‐scale companies, operating in different industry segments. The study resulted in a list of success factors, including not only characteristics and capabilities existing within a test environment (intrinsic success factors) but also properties not inherent to the test environment, but still vital for a successfully implemented test environment (extrinsic success factors). This distinction is important, as the root causes differ and as addressing them requires distinct approaches—not only of technology but also of organization, communication and collaboration. We find that successful implementations of test environments for large‐scale software systems depend primarily on how they support the company's business strategy, test organization and product testability (extrinsic success factors). Based on this, test environments can then be optimized to improve test environment capabilities, usability and stability (intrinsic success factors). The list of intrinsic and extrinsic success factors was well received by all five companies included in the study, supporting that the intrinsic and extrinsic success factors for test environments can be applied to a large segment of the software industry. Abstract : Successful implementations of test environments for large‐scale software systems depend primarily on how they support the company's business strategy, test organization and product testability (extrinsic success factors). Based on this, test environments can then be optimized to improve test environment capabilities, usability and stability (intrinsic success factors).